DIFFERENCE AMOUNT OF COLIFORM AND E. COLI BACTERIA FOUND IN DOGS WITH DIARRHEA AND HEALTHY DOGS - Veronica, Leny Beatry; Suarjana, I Gusti Ketut; Gelgel, Ketut Tono Pasek (Buletin Veteriner Udayana, 2023)
This research is conducted to find out the number of Coliform bacteria in dogs that suffer diarrhea and healthy dogs. This research utilizes 20 recent feces of dogs, consist of 10 healthy dogs and 10 dogs with diarrhea. The sample is put in Eosin Methylene Blue Agar media using scattering method. The data of Coliform colony is analyzed using Paired Sample T-Test measurement to find the average value. The result of this research shows that the number of Coliform and E. coli bacteria in dogs with diarrhea is greater than in healthy dogs. The average number of Coliform in dogs with diarrhea are 2.7 x 10 9 CFU/g and healthy dogs 3,7 x 10 7 CFU/g. Next, as for the average number of E. coli in dogs with diarrhea are 2,6 x 10 9 CF/g and healthy dogs 2,8 x 10 7 CFU/g.